2005
DOI: 10.1111/j.1365-2567.2005.02246.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction and recall of immune memory by mucosal immunization with a non‐toxic recombinant enterotoxin‐based chimeric protein

Abstract: SummaryPrevious reports have suggested that peroral delivery of antigens chemically coupled to non-toxic recombinant enterotoxin B subunits, such as the cholera toxin B subunit (CTB), induces tolerance to the antigen that may be abrogated by the toxic enzyme activity of intact enterotoxins, such as cholera toxin (CT). The aim of this study was to examine the immunogenicity of a genetically coupled protein composed of the saliva-binding region (SBR) of the Streptococcus mutans surface antigen AgI/II and the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
20
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 51 publications
4
20
0
Order By: Relevance
“…The presence of IsdA-specific IgA in nasal, intestinal, and vaginal fluids after intranasal immunization with IsdA-CTA 2 /B suggests that IgA blasts migrated from the nasalassociated lymphoid tissue into distal mucosal effector sites in the nasal passage and gastrointestinal and genital tracts. Induction of T lymphocyte proliferation by IsdA-CTA 2 /B is consistent with previous studies showing that CT (16,18,40,62). These reports also support our findings that CT and CT derivatives promote more of a Th2-type response.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The presence of IsdA-specific IgA in nasal, intestinal, and vaginal fluids after intranasal immunization with IsdA-CTA 2 /B suggests that IgA blasts migrated from the nasalassociated lymphoid tissue into distal mucosal effector sites in the nasal passage and gastrointestinal and genital tracts. Induction of T lymphocyte proliferation by IsdA-CTA 2 /B is consistent with previous studies showing that CT (16,18,40,62). These reports also support our findings that CT and CT derivatives promote more of a Th2-type response.…”
Section: Discussionsupporting
confidence: 82%
“…Lastly, this report supports the hypothesis that the humoral and cellular responses induced by IsdA-CTA 2 /B are superior to those stimulated by a mixed preparation of antigen and adjuvant (IsdA plus CTA 2 /B). Thus, the structure of the IsdA-CTA 2 /B chimera is optimal for the induction of antigen-specific humoral responses and potentially for presentation on MHC molecules, which is consistent with previous reports of chimeric molecules using distinct antigens (18,36,51). CT and the closely related LTI are gold-standard mucosal adjuvants with a long history of use in animals and more recent use of nontoxic derivatives in humans.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Numerous studies in experimental animal models have shown that immunization with AgI/II can induce specific salivary IgA antibody responses that inhibit S. mutans colonization and protect against dental caries (25,46,50). Furthermore, in our previous studies (14) and those of others (12), it was shown that the 42-kDa salivabinding region (SBR) of AgI/II also exhibits good immunogenicity in inducing specific salivary IgA response.…”
mentioning
confidence: 99%